Chapter 2 Which Way Does It Go between You Two? Modes of Interdisciplinary Intervention - Fitzgerald, Des (Springer Nature, 2015)
This book offers a provocative account of interdisciplinary research across the neurosciences, social sciences and humanities. Setting itself against standard accounts of interdisciplinary 'integration,' and rooting itself in the authors' own experiences, the book establishes a radical agenda for collaboration across these disciplines. Rethinking Interdisciplinarity does not merely advocate interdisciplinary research, but attends to the hitherto tacit pragmatics, affects, power dynamics, and spatial logics in which that research is enfolded. Understanding the complex relationships between brains, minds, and environments requires a delicate, playful and genuinely experimental interdisciplinarity, and this book shows us how it can be done.